Response of sheep fed on concentrate containing feather meal and supplemented with mineral Chromium - D, Yulistiani; W, Puastuti; IW, Mathius (Indonesian Journal of Animal and Veterinary Sciences, 2013)
A study was conducted to evaluate the effect of substitution of protein concentrate with feather meal supplemented with organic chromium mineral on performance of lambs. Twenty five male lambs were fed basal feed of fresh chopped king grass ad libitum and were allotted to either one of five different supplements (five dietary treatments): Control (C); 10% of protein in concentrate was substituted by feather meal (FM); 10% of protein in concentrate was substituted by feather meal supplemented with Cr yeast at 1.5 mg (FMCrOrg); 10% of protein in concentrate was substituted by feather meal supplemented with Cr inorganic which equal to the amount of Cr bound in yeast (FMCr); Concentrate control supplemented with 1.5 mg Cr yeast (CCrOrg). Cr-organic was synthesized by incorporating CrCl3 in fermented rice flour by Rhizopus sp. The mineral is mixed with feather meal as a mineral carrier. Sheep in all treatments received iso protein concentrate. Parameters observed were body weight change, feed consumption and nutrient digestibility. Results shows that there was no significant effect of diet treatments on average daily gain (ADG), dry matter consumption and feed conversion, with the average value of 75.4 gr/day; 74.9 g/BW0.75 and 9.9 respectively, However diet treatment of organic chromium and protein substitution with feather meal (FMCrOrg) showed tendency of having higher ADG (83.57 g/h/d). Average nutrient digestibility of dry matter, organic matter and NDF were 68.7; 69.6 and 60.9%, respectively. However NDF digestibility of FMCrOrg tended to be higher than other treatment (67.0%). It is concluded that partial substitution of protein concentrate by feather meal and 1.5 mg Cr-organic supplementation did not affect sheep performance. Key Words: Chromium, Sheep, Feather Meal, Supplementation